ANALYSIS ON 85 CASE REPORTS OF ADVERSE DRUG REACTIONS - Jin, Xiang-qiu; Min, Lian-qiu (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
This study investigated the occurrence and characteristics of adverse drug reactions (ADR) in our hospital and provide references for clinical rational drug use. We collected the 85 case reports of adverse drug reactions in our hospital in 2010 and made retrospective statistical analysis on them. The varieties of anti-infective drugs used are the most used. It also had the highest proportion of adverse drug reactions; the common symptom of adverse drug reactions is skin and accessory damage. Adverse drug reactions are affected by many factors, and relevant departments should strengthen ADR monitoring, to reduce or avoid the occurrence of adverse drug reactions.